Description, redescription and revision of sixteen putatively closely related species of Echinoderes (Kinorhyncha: Cyclorhagida), with the proposition of a new species group – the Echinoderes dujardinii group - Sørensen, Martin V.; Goetz, Freya E.; Herranz, María; Chang, Cheon Young; Chatterjee, Tapas; Durucan, Furkan; Neves, Ricardo C.; Yildiz, N. Özlem; Norenburg, Jon; Yamasaki, Hiroshi (European Journal of Taxonomy, 2020)
Thirteen species of Echinoderes with nearly identical spine/tube patterns, and apparently similar tergal extensions were re-examined and compared. Based on this, redescriptions and/or emended species diagnoses are provided for Echinoderes aureus, E. dujardinii, E. gerardi, E. imperforatus, E. pacificus, E. pilosus, E. sensibilis, E. sublicarum and E. worthingi, and new details about cuticular structures are added for E. kozloffi and E. gizoensis. The new information derived from the redescriptions, and the subsequent comparative studies revealed that: 1) the holotype of Echinoderes lanceolatus is identical with the types of Echinoderes aureus, and E. lanceolatus is thus a junior synonym of E. aureus; other potentially synonymous species that should be addressed further in the future include: E. dujardinii + E. gerardi; E. imperforatus + E. sensibilis, and E. pacificus + E. sublicarum; 2) the paratypes of E. lanceolatus represented a different yet undescribed species, here described as E. songae Sørensen & Chang sp. nov.; 3) a comparison with literature information about E. ehlersi showed that the species is so insufficiently described that a redescription of topotype material is required before the species should be considered for taxonomic comparison; 4) specimens from the Andaman Islands, India, that previously have been reported as Echinoderes cf. ehlersi represent two different undescribed species, of which one is described as E. chandrasekharai Sørensen & Chatterjee sp. nov. and the other is left undescribed due to the limited material available; 5) out of a total of fifteen addressed species, it is proposed that eleven represent a putatively monophyletic group that is named the Echinoderes dujardinii group. The group includes following species: E. dujardinii, E. ehlersi, E. gerardi, E. imperforatus, E. kozloffi, E. sensibilis, E. pacificus, E. sublicarum, E. songae Sørensen & Chang sp. nov., E. chandrasekharai Sørensen & Chatterjee sp. nov., and Echinoderes sp. from the Andaman Islands, and is supported by a similar spine/tube pattern (except for variation regarding the presence of lateral accessory tubes on segment 8); generally short middorsal spines, especially on segments 4 to 6; glandular cell outlets type 1 always present in middorsal positions on segments 1 to 3, and in subdorsal positions on segments 4 to 9; glandular cell outlets type 2 always present in laterodorsal or midlateral positions on segment 8, and sometimes in same positions on segment 9 but never at any other segments or positions; female papillae always present on sternal plates of segments 7 and 8, and occasionally also on segment 6; tergal extensions well-spaced, triangular, gradually tapered cones, and pectinate fringes of sternal extensions are differentiated into seta-like tufts. The comparisons furthermore showed potential taxonomic significance of two echinoderid character traits that previously have been slightly neglected as diagnostic traits, namely the presence and appearance of female papillae, and the dorsal pattern of glandular cell outlets type 1. Female papillae may occur on the sternal plates of segments 6 to 8, but the positions may differ from ventrolateral to ventromedial, and the morphology of the intracuticular substructure also differ at species level. Information about position and morphology of female papillae proved helpful for species recognition, but it might also provide information of phylogenetic importance. Analyses of glandular cell outlet type 1 patterns on the dorsal sides of segments 1 to 9 in species of Echinoderidae, revealed several apparently unique or rare patterns, but also three distinct patterns that applied to larger groups of species. One pattern is the one present in all species of the E. dujardinii group, whereas the other two common patterns included 1) middorsal outlets on segments 1 to 3, and paradorsal outlets on segments 4 to 9 (found in 27 species), and 2) middorsal outlets on segments 1 to 3, 5 and 7, and paradorsal outlets on segments 4, 6 and 8 to 9 (found in 27 species)